The effects of tranexamic acid and 6% hydroxyethyl starch (HES) solution (130/0.4) on postoperative bleeding in coronary artery bypass graft (CABG) surgery - Yanartas, M (Int J Clin Exp Med, 2015)
Background: The addition of 6% hydroxyethyl starch (HES) into Ringer lactate priming solution may have adverse effects on hemostasis in patients undergoing coronary artery bypass grafting (CABG) with cardiopulmonary bypass (CPB) with or without the use of tranexamic acid. Methods: In a prospective, randomized clinical trial, 132 patients were assigned to receive 20 ml/kg of Ringer priming solution with or without tranexamic acid (TA) (Group RS-TA, n=34 and Group RS-noTA, n=32) or 10 ml/kg of 6% HES plus 10 ml/kg of RS priming solution with or without intravenous tranexamic acid (Group HES-TA, n=35 and Group HES-noTA, n=31). Estimated blood loss, chest tube drainage, amount of blood products, hemoglobin, hematocrit, platelet and coagulation parameters were examined before and 24 hour after surgery. Results: For Group HES with tranexamic acid, when compared to other groups, estimated blood loss, postoperative 24 hour drainage loss and blood product transfusions were less (P=0.023; P=0.003; P=0.001; respectively) and hemoglobin, hematocrit values at 12 and 24 hours after surgery increased in comparison to other groups (P=0.041, P=0.034, P=0.004, P=0.001; respectively). Platelet concentrations were similar between groups (P>0.05). Conclusions: In CABG, the administration of tranexamic acid in HES 130/0.4 prime solution study group decreased estimated blood loss and chest tube drainage in comparison to patients receving Ringer prime solution with or without tranexamic acid postoperatively however, no effects on renal functions or postoperative complications were shown.